Visual adaptation could aid sympatric speciation in a deep crater lake - Karen L. Carleton; Daniel Escobar‐Camacho; Thomas D. Kocher (Molecular Ecology, 2019)
Allopatric speciation was originally suggested to be the primary mechanism of animal speciation (Mayr, 1942; Figure 1). During allopatric speciation, populations diverge when gene flow is reduced across significant biogeographic barriers. Sympatric speciation, where species diverge while inhabiting the same location, was thought to be essentially impossible. However, the advent of theoretical models followed by new experimental evidence made sympatric speciation more plausible (Via, 2001). The cichlid fishes of Barombi Mbo, a small crater lake in western Cameroon, became one of the most widely accepted examples of sympatric speciation (Schliewen, Tautz, & Paabo, 1994). Although the phylogenetic history of this clade is not quite as simple as originally thought, it remains one of the best examples of sympatric speciation (Richards, Poelstra, & Martin, 2018). However, little is known about the molecular mechanisms contributing to the splitting of these species in situ. In a From the Cover article in this issue of Molecular Ecology , Musilova et al. (2019) focus on the diversity of visual systems among these fishes. They identify genetic changes associated with several aspects of visual adaptation that may have contributed to the ecological specialization and sympatric speciation of cichlids in this lake.